2010
DOI: 10.1080/15389581003735626
|View full text |Cite
|
Sign up to set email alerts
|

A Roadside Survey of Alcohol and Drug Use Among Drivers in British Columbia

Abstract: The finding that drug use is more common than alcohol use among drivers highlights the need for a unique and separate societal response to the use of drugs by drivers commensurate with the extent of safety risks posed to road users. The observed differences between driving after drug use and driving after drinking have implications for enforcement and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 6 publications
4
28
0
5
Order By: Relevance
“…Estudos realizados em outros países, com metodologia similar, apresentam taxas de 5% a 14% nas noites dos ns de semana 14,15 . A análise das características dos condutores em todas as regiões do estado não apresentou diferença estatística, apontando para uma homogeneidade da população pesquisada.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estudos realizados em outros países, com metodologia similar, apresentam taxas de 5% a 14% nas noites dos ns de semana 14,15 . A análise das características dos condutores em todas as regiões do estado não apresentou diferença estatística, apontando para uma homogeneidade da população pesquisada.…”
Section: Discussionunclassified
“…A amostra do presente estudo teve predominância do sexo masculino e idade entre 18 e 30 anos, com média de idade de 31 anos. Estudos com metodologia similar têm apresentado essas mesmas características dos condutores nas noites dos ns de semana 13,14 . Além disso, os indivíduos da população em estudo tinham bom nível de educação e renda.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…World Health Organization reported that, approximately 1.3 million people die each year on the world's roads and between 20-50 million people sustaining non fatal injuries (WHO., 2009). Indeed, drivers who drive under the influence of drugs represent major threat to themselves and others on the road (Beirness and Beasley, 2010). To address the significance of this problem, Mathers et al (2004) reported that, road traffic injuries are highly comparable to the number of deaths resulting from communicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In France in 2001-2003, 7% of drivers involved in fatal road crashes were positive for cannabis [4] and 6% of drivers involved in road crashes in a series from Italy were positive for drugs, mostly opiates, cannabis, and cocaine [5]. In a survey evaluating the prevalence of drug driving in British Columbia, 10% of randomly selected drivers were tested positive for cannabis in oral fluid [6]. Driving under the influence of cannabis is associated with the perpetration of serious road-rage behaviour, as well as experiencing road-rage victimization and perpetration [7].…”
Section: Introductionmentioning
confidence: 99%